(untitled) (Mustansiria Dental Journal, 2018)
The biological objectives of root canal treatment have not changed over the recent decades, but the methods to attain these goals have been greatly modified. The introduction of NiTi rotary files represents a major leap in the development of endodontic instruments, with a wide variety of sophisticated instruments presently available (1, 2). Whatever their modification or improvement, all of these instruments have one thing in common: they consist of a metal core with some type of rotating blade that machines the canal with a circular motion using flutes to carry the dentin chips and debris coronally. Consequently, all rotary NiTi files will machine the root canal to a cylindrical bore with a circular cross-section if the clinician applies them in a strict boring manner